Arcade Games and Childhood: When Computational Technology Became Play: Quando a tecnologia computacional virou brincadeira (TEL Tempo, Espaço e Linguagem, 2026)
This article seeks to conduct an analysis of the arcade game houses that began to be installed along the avenues of the city of São Paulo in the 1970s and the impact of this phenomenon on the concerns of families and authorities who attempted to understand how video games could influence youth. At the same time, it analyzes the functioning of these new entertainment media, their relationship with the computer industry, and the transformations they stimulated in forms of sociability and in the dynamics of interaction between individuals and technology. As a source, the article A cidade se diverte. Ao fliperama!, by journalist Fausto Macedo, published in 1977 in Jornal da Tarde, was used. To enrich the debate on games and video games, works by Johan Huizinga and Christopher A. Paul were also used.Keywords: video game; arcade; technology.